Use of scanning electron microscopy to analyze sculpturing pattern and internal features of pollen grain wall in some members of Astragaleae (subfamily: Papilionoidae). Issue 5 (17th December 2021) - Rashid, Neelam; Zafar, Muhammad; Ahmad, Mushtaq; Malik, Khafsa; Shah, Syed Nasar; Sultana, Shazia; Zahid, Nafeesa; Noshad, Qumqum; Siddiq, Zafar
Abstract: Palynological features of tribe Astagaleae L. have been observed with scanning electron microscopy (SEM), to assess features that can be used to re‐examine the placement and taxonomic position of tribe. The palynomorph attributes of 10 species included in three genera of Astragaleae ( Astragalus L., Glycyrrhiza L., and Oxytropis DC.) are investigated. The assignment of genus Oxytropis in tribe Astragaleae was also reevaluated based on pollen characters. Pollen appear to be prolate, prolate‐spheroidal, and subprolate. Polar axis size (P) varies from 31.3 μm ±1 to 17.5 μm ±1.4 and equatorial axis size (E) varies from 22.2 μm ±1.8 to 13.1 μm ±0.9. Prominent apertures found consistently dispersed along the surface of pollen. Three kinds of ornamentation pattern were recorded, that is, reticulate or reticulate‐perforate and perforate. The studied species display variation in equatorial and polar diameter, aperturation and sculpturing pattern, exine thickness, and pollen shape. On the basis of descriptive pollen features, a dichotomous taxonomic key and UPGMA analysis has been made for effortless and quick identification. The study concluded that disparities of the entire features are typically unrelenting and concerned with the species and shows potential systematic significance. The combination of palynological attributes in association with additional traits has prospective for systematic identification at species and genus level. Abstract : Pollen features of some species of Astragalus, Glycyrrhiza, and Oxytropis are described. Pollen grains exhibit variation in shape, size, sculpturing, and ornamentation pattern. A dichotomous taxonomic key has been developed for effortless and quick identification. UPGMA analysis dependent on descriptive features also depict groupings among Astragaleae members.